A general simulation procedure for the electrical characteristics of metal-insulator-semiconductor tunnel structures - Vexler, M. I. (2013)
The algorithm is suggested for calculating the I–V characteristics of a voltage- or current-controlled metal-tunnel-thin insulator-semiconductor system. The basic underlying physical models are discussed. Applicability of the algorithm is confirmed by a comparison of the simulation results with the measurement data obtained by the authors and borrowed from the literature, for several different structures. The presented information is supposed to suffice for calculating the electrical characteristics of the investigated structures with the various combinations of materials: metal or polysilicon gate, single-layer or stacked insulator, and semiconductor with any doping type and level.